Korelasi Model Pembelajaran CORE (Connecting, Organizing, Reflecting, Extending) dan Kemampuan Menulis Cerpen - Audina, Fitra; Putri Aprilia , Siti; Aramitha Lubis , Syifa; Rizki Amanda , Dila (PT. ALHAFI BERKAH INDONESIA, 2023)
Students' capacity to create short tales is related to their proficiency in the CORE (Connecting, Organizing, Reflecting, and Extending) learning framework, which is the focus of this study. Participation from a cross-section of high school students allowed for the use of quantitative research methods. Students' perspectives on the use of the CORE stages in learning to create short stories and their growth in short story writing abilities are assessed primarily via the use of an inquiry. Statistical study revealed a favorable correlation between using the CORE model and students' improved writing skills.